A charcoal-shaped catalyst NiFe2O4/Fe2O3 in electro-Fenton: high activity, wide pH range and catalytic mechanism. Issue 13 (7th June 2021) - Zheng, Yanshi; Qiu, Shan; Deng, Fengxia; Zhu, Yingshi; Ma, Fang; Li, Guojun
ABSTRACT: A charcoal-shaped catalyst NiFe2 O4 /Fe2 O3 in electro-Fenton (EF) was synthesized by a facile precipitation approach via sintering products of oxalate co-precipitation. This obtained NiFe2 O4 /Fe2 O3 catalyst was easily separated via an external magnetic field and was used as a heterogeneous electro-Fenton catalyst for rhodamine B (RhB, a target pollutant) degradation. Characteristics of NiFe2 O4 /Fe2 O3 catalyst were assessed using scanning electron microscope (SEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and Barrett-Emmett-Teller (BET), respectively. SEM results revealed that the proposed NiFe2 O4 /Fe2 O3 was charcoal-shaped with the size in the range of 0.5–5 μm. Experiment results show that the EF process with the proposed catalyst could work in a wide pH range from 3 to 9. Under optimized conditions, estimated 90% RhB degradation was achieved in 60 min under the following conditions: 0.6 g/L NiFe2 O4 /Fe2 O3, pH 3. Radical scavengers and electron spin resonance (ESR) spectra results demonstrated that the main oxidant species involved was ⋅ OH, accounting for RhB degradation in EF. Moreover, according to our research on interfacial reaction, ⋅ OH was mainly generated from the homogenous Fenton reaction rather than the surface Fenton reaction, stimulating by the dissolved Fe 2+, Fe 3+ and Ni 2+ from catalyst. The reusability of NiFe2 O4 /Fe2 O3 catalyst was evaluated for recycling the same catalyst for 5 runs. In conclusion, the facile fabrication NiFe2 O4 /Fe2 O3 catalyst shows great potential in wastewater treatment with promising activity. GRAPHICAL ABSTRACT: UF0001